Panchayati raj and the tribal development in West Bengal - Mallick, Md. Ayub (2012)
The paper examines the Panchyati Raj Institutions in West Bengal with explanatory outlook and observes that the poorest of the poor are not represented properly. The influential sections in the rural society are gaining the ground. The tribal people are not actually represented. Inspite of its changing character like transparent bureaucracies Panchayats have failed in the fields of extensive socio-economic mobilization and the innovative suggestions like the setting up of rural industries, ecological initiatives, housing, the improvement of the position of women and STs, and the establishment of co-operatives have got only rarely mentioned as priority objective of the work of Panchayats. Despite various development measures under the Panchayat Samities, actual development of the tribal people of West Bengal did not take place. Indebtedness has become the regular feature of their life process, resulted in the culmination of four interrelated consequences: deterioration in resources, technological change without change in the quantum of total resources and the consumption pattern, stagnation in production relations, but rapid changes in technology and consumption pattern leading to progressive destitution of the tribals, and stagnation in resource position, technology and productive relations, but rapid changes in the consumption pattern. The development programmes are not flexible. - Reproduced.
Keywords: Tribes - India - West Bengal; Panchayat - India - West Bengal; Panchayat